2019
DOI: 10.1039/c9ta08754k
|View full text |Cite
|
Sign up to set email alerts
|

Carrot-inspired solar thermal evaporator

Abstract: A carrot-inspired solar thermal evaporator exhibits a water evaporation rate of 2.04 kg m−2 h−1 and an outstanding durability and stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
64
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(64 citation statements)
references
References 39 publications
0
64
0
Order By: Relevance
“…The surface temperature of SHCSC under different light intensities is shown in Figure S4, Supporting Information. The evaporation rate of SHCSC is remarkably superior to those of high‐temperature carbonized biomass materials under 1 sun (Table S4, Supporting Information) [16d,17,18,23,25] . The surface temperature of SHCSC was measured by an IR camera.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface temperature of SHCSC under different light intensities is shown in Figure S4, Supporting Information. The evaporation rate of SHCSC is remarkably superior to those of high‐temperature carbonized biomass materials under 1 sun (Table S4, Supporting Information) [16d,17,18,23,25] . The surface temperature of SHCSC was measured by an IR camera.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the concentrations of Na + , Mg 2+ , K + , and Ca 2+ after desalination were only 0.6094, 0.0236, 0.2099, and 0.2785 mg L −1 (less than the World Health Organization [WHO] drinking water standards of 50, 100, 10, and 100 mg L −1 ), respectively. [ 18 ] The ion reduced ratio is above 99.9% (Table S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] A low‐cost carbonized carrot solar evaporator can achieve an apparent evaporation rate of 2.04 kg m −2 h −1 under 1.0 sun due to the sufficient water transportation enabled by the inherent structure. [ 12 ] Apart from taking advantage of the intrinsic structure of biomass, elaborate architecture design of biomass is a promising path to promote solar evaporation. Arched bamboo charcoal was investigated to be endowed with broadband light absorption, high evaporation efficiency of 84% under 1 sun radiation, as well as superb stability under various ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Recently, the carbonization of varieties of plants and related products has been utilized to design SVGs. [37][38][39][40][41] The unique structure of the plant stem works as channels for conducting water in these SVGs. But, the carbonization of plants required high-temperature annealing under a controlled environment.…”
mentioning
confidence: 99%